Universty extesion actions at the Pé da Serra settlement, Nova Xavantina - MT - Fernandes Silva, Dilson Lucas; Maia, Ana Heloisa; Nunes de Souza Fernandes, Delvani; Cavalcanti da Silva, Flaviana; de Souza, Manoel Euzébio (Guará Journal, 2017)
The production of knowledge via extension, it would make the exchange of systematized, academic and popular knowledge, resulting in the democratization of knowledge. This work aims to analyze the university extension actions by Agronomia course students Unemat Campus of Nova Xavantina, the settlement foot of the mountain. We interviewed 10 farmers through specific questionnaire, which sought to prioritize the actions taken, their power between farmers, the main difficulties encountered by families for practical application of the techniques, and other aspects relatedto the topic of interest to the project. From the results obtained in this study, it can be seen that the involvement of students in the problems of farmers in the settlement Pé da Serra, has contributed to the strengthening of relations between farmers, academicsand researchers, as well as exchanges of experience has allow a better return on university extension actions. The establishment of a process of knowledge between the parties involved, the positive and negative aspects pointed serve as a basis for building joint solutions that can be started from the university to the community and/or vice versa, in order to reach the proposed goals the Extension Project.
Keywords: Family farming; Rural extension; Rural settlements; University